Kandungan Fenol Pada Cascara Kopi Produksi Home Industri di Karo - Prasetyo, Healthy Aldriany; Winardi, Rafael Remit (Program Studi Pendidikan Biologi, 2024)
Cascara is made from coffee skins and is starting to be known as a health drink. There are four varieties of coffee cultivated in Karo and the skins are used as Cascara. The aim of this research was to determine the phenol levels associated with the properties of Cascara originating from varieties cultivated in Karo. The method to obtain the phenol content in Cascara uses maceration using 85% methanol on dry Cascara. The research results show that Cascara which comes from Andungsari coffee skins has the highest phenol content, namely 8.0952 mg GAE/g and the lowest in Cascara Siagarrutang at 5.1515 mg GAE/g.